Pendampingan Berkelanjutan terhadap Pengembangan Pariwisata Desa Selopamioro - Yulita Kusuma Sari (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2019)
Tourism development in rural areas with the method of community participation is an ideal condition that can be achieved on the basis of community spirit as basic and primary capital, supported by the availability of natural and cultural resources, good governance and supported by academics or other institutions as facilitators. In terms of developing tourism in Selopamioro Village, the study program of Tourism, Faculty of Cultural Sciences, Universitas Gadjah Mada acts as a supporting actor, through sustainable community service activities. Sustainability is important in developing tourism villages, it is intended that there is integration between activities carried out from year toyear. Continuous mentoring are carried out from November 2016 until the end of 2018. Tere are signifcant developments from the existence of tourist attractions, especially natural tourism, and tourist accommodation in the form of homestays. Using the potential of institutional networks, the study program of Tourism collaborate with students, alumni, and hoteliers to jointly transfer knowledge to the community as owners and managers of tourist destinations. Interaction with the community through direct discussions in joint forums, or representatives from the arts community, PKK associations, youth associations, and tourism conscious groups. Te results of the activity show that the assistance in developing sustainable tourism is able to build the spirit of the community to continue to participate in villagetourism development. Te spirit is the next capital of hard work, by utilizing institutional networks, the strength of the younger generation, village government support, and social media, the community has succeeded in generating new tourist attractions, improving accommodation facilities, and better tourism management.=================================================================Pengembangan pariwisata di perdesaan dengan metode partisipasi masyarakat merupakan sebuah kondisi ideal yang dapat tercapai atas dasar semangat masyarakat sebagai modal dasar dan utama, didukung oleh tersedianya sumber daya alam dan budaya, pemerintahan yang baik, dan didukung oleh akademisi atau lembaga lain sebagai fasilitator. Dalam hal pengembangan pariwisata di Desa Selopamioro, Prodi Pariwisata FIB UGM berperan sebagai aktor pendukung melalui kegiatan pengabdian masyarakat yang berkelanjutan. Berkelanjutan penting dalam pengembangan desa wisata. Hal tersebut dimaksudkan agar ada integrasi antarkegiatan yang dilaksanakan dari tahun ke tahun. Kegiatan pendampingan berkelanjutan dilaksanakan mulai November 2016 hingga akhir 2018. Tercatat perkembangan yang signifkan dari keberadaan daya tarik wisata, khususnya wisata alam, dan akomodasi wisata berupa homestay. Menggunakan potensi jejaring kelembagaan, Prodi Pariwisata menggandeng mahasiswa, alumni, dan pihak perhotelan untuk bersama-sama melakukan transfer pengetahuan kepada masyarakat sebagai pemilik sekaligus pengelola destinasi wisata. Interaksi dilakukan bersama masyarakat melalui diskusi langsung dalam forum bersama, yakni bersama perwakilan dari komunitas seni, perkumpulan PKK, perkumpulan pemuda, dan kelompok sadar wisata (pokdarwis). Hasil kegiatan menunjukkan bahwa pendampingan pengembangan pariwisata secara berkelanjutan mampu membangun semangat masyarakat untuk terus berpartisipasi dalam kegiatan pengembangan pariwisata desa. Semangat tersebut yang menjadi modal kerja keras selanjutnya, dengan memanfaatkan jejaring kelembagaan, kekuatan generasi muda, dukungan pemerintah desa, dan media sosial, masyarakat berhasil memunculkan atraksi wisata baru, memperbaiki fasilitas akomodasi, serta manajemen pariwisata yang lebih baik.